Analisis Kerentanan Pulau-Pulau Kecil di Kecamatan Togean Kabupaten Tojo Una Una Provinsi Sulawesi Tengah (Studi Kasus P. Kukumbi, P. Enam, P. Mogo, P. Kadidiri, P. Pagempa, P. Tongkabo) - Mohamad Akbar (Journal Omni-Akuatika, 2016)
This research was conducted in small islands area to Togean District, TojoUna-Una Regency Central Celebes by ecological and sosio-economic approach.  Methods those used in this research were vulnerability index, MCDM (multi criteria dimension making) and Geographycal information system (SIG) approach.  Data was collected bt participative and explorative approach.  Data analysed parameters using vulnerability, assessment method involved vulnerability variable parameters i.e. area characteristic, area degradation, sea level rise, human impact, economic exposure, economic remoteness.  The results shows the range ofcomposit vulnerability index for ecological (CVI-Ek) is 0.00-0.77, economic (CVI-En) is 0.00-0.75, and composite vulnerability ecological-economic (CVI-EE) is 0.00-0.76.  Enam island (0.76)and tongkabo island (0.66) is rated to high vulnerable (0.67), Mogo Island (0.14), Kukumbi Island (0.12), Pagempa Island (0.09) and Kadidiri Island (0.07), is considerednon vulnerable.  MCDM analysis result that is used to determine small island management model in Togean District, shows ecological criteria is most important compared with economy criteria and social criteria.  Analysis of SMART technique  shows the type small islands  sustainability management  scenario in Togean District, those are scenario A (adaptation, 0.94) and scenario B ( without adaptation, 0.55).Keywords : small island, composite vulnerability index, sustainability, togean district.